Effects of cartilage-supporting nutritional supplementation on knee osteoarthritis symptoms and quality of life in a 12-week randomized double-blind placebo-controlled pilot study - Johannes-Paul Fladerer-Grollitsch; Thomas Klein; Albert Kompek; Nicole Steiner; Daniel Menzel; Christiane Schön (Scientific Reports)
Abstract Osteoarthritis (OA) is a prevalent degenerative joint disease, often affecting the elderly, characterized by cartilage degradation and bone remodelling, leading to pain, stiffness, and impaired movement. This 12-week, randomized, double-blind, placebo-controlled pilot study investigated the efficacy of a formulation containing collagen type II, glucosamine hydrochloride and chondroitin sulfate, in alleviating knee OA symptoms in subjects with mild to moderate knee pain. Fifty-four participants were enrolled, with 52 completing the study. Participants were assessed using the Knee injury and Osteoarthritis Outcome Score (KOOS), performance-based physical function tests and global assessment tests. Results indicated significant improvements in the verum group compared to placebo. KOOS subscales showed improvements in symptoms (8.16%, p < 0.05), sport/recreation (25.25%, p < 0.01), and quality of life (27.66%, p < 0.001). Stiffness improved by 14.68% (p < 0.05) in the verum group. Both groups exhibited significant pain reduction (KOOS pain, p < 0.001 and p < 0.01 for verum and placebo, respectively). Performance-based measures, such as the Chair Stand test, improved significantly in both groups, though other metrics showed no significant differences. The verum group exhibited a linear improvement over 12 weeks, contrasting with the placebo group’s initial response and subsequent plateau. SF-36 Physical Component scores improved in both groups (p < 0.05), but mental health scores remained unchanged. Global assessment favoured the verum group, with more participants reporting OA improvement and recommending the product (p < 0.01). Biomarkers hsCRP and COMP showed no significant changes, likely due to sample variability. While the study did not achieve its primary endpoint, the nutritional formulation demonstrated an excellent safety profile and encouraging improvements in patient-reported symptoms and quality of life, warranting larger confirmatory trials. Registration number: DRKS00029563 05/10/2022